EKSPLORASI PERSEPSI DAN KESIAPAN PARTISIPASI MASYARAKAT TERHADAP RENCANA PENDIRIAN KOPERASI MERAH PUTIH : STUDI KUALITATIF DI DESA KURAI TAJI, KOTA PARIAMAN - Permata Sari, Rossy Endah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article aims to explore the initial perceptions and readiness of the community to participate in the planned establishment of Koperasi Merah Putih (Red and White Cooperative) in Kurai Taji Village, Pariaman City. This initiative is part of a national government program designed to strengthen community-based economic systems, and it is scheduled to be officially launched in December 2025. Employing a descriptive qualitative approach, this study investigates the thoughts, attitudes, and expectations of local residents through in-depth interviews, social observation, and relevant documentation. The findings indicate that most community members express enthusiasm toward the establishment of the cooperative as a means of promoting local economic empowerment. However, a lack of information and limited understanding of cooperative mechanisms still hinder their full readiness for active involvement. Therefore, adaptive and participatory communication strategies are necessary to ensure the successful implementation of this cooperative in the near future. Keywords : cooperative, community perception, participation readiness, village economic development, qualitative study.